2018
DOI: 10.1093/ageing/afy002
|View full text |Cite
|
Sign up to set email alerts
|

Improved hearing in Swedish 70-year olds—a cohort comparison over more than four decades (1971–2014)

Abstract: Objectivethe world population is ageing rapidly. In light of these demographic changes, it is of interest to generate current data regarding the prevalence and characteristics of age-related hearing loss. The purpose of this study was to investigate hearing acuity and the prevalence of hearing loss in a contemporary age-homogenous cohort of old adults, and to assess secular trends in hearing function during the last half-century (1971–2014).Methodswe performed a prospective population-based cohort comparison s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 22 publications
3
29
1
Order By: Relevance
“…If less noise exposure in Cohort 1930 was the only reason for improved hearing among 85-year-old men, a statistically significant better hearing acuity at age 75 would be expected. Another study within H70 (Hoff et al 2018) described similar hearing acuity for pure-tone hearing thresholds among 70-yearold men and women born in 1901-1902 and 1922. This indicates further reasons for the improvement in men's hearing than a lower level of exposure to noise.…”
Section: Factors Behind the Improvement In Hearing Acuity Among Menmentioning
confidence: 78%
“…If less noise exposure in Cohort 1930 was the only reason for improved hearing among 85-year-old men, a statistically significant better hearing acuity at age 75 would be expected. Another study within H70 (Hoff et al 2018) described similar hearing acuity for pure-tone hearing thresholds among 70-yearold men and women born in 1901-1902 and 1922. This indicates further reasons for the improvement in men's hearing than a lower level of exposure to noise.…”
Section: Factors Behind the Improvement In Hearing Acuity Among Menmentioning
confidence: 78%
“…Results derived in the pooled sample were compared to findings reported for the Dutch Rotterdam study [10], the most recent results for the Swedish Gothenburg study [6], the US-American NHANES cycles 1999-2004 [25,4], the cycles 1999 to 2006 [26], and the cycles 2011 to 2012 [5]. Although principally eligible for comparison, the HTL estimates for an earlier Gothenburg cohort were not included in this comparison because the authors stated HTL deviations to earlier cohorts that possibly originated from "differences regarding ambient noise levels in the test rooms used, in combination with difficulties for less experienced testers to detect the problems that arise close to 0 dB HL in a non-insulated test room" [7].…”
Section: Adjustments For Comparison To International Resultsmentioning
confidence: 99%
“…This trend towards lower HTL and HI in US-American surveys was also observed in current European data. Based on the data sampled in the Gerontological and Geriatric Population Study in Gothenburg, a longitudinal study on the health of 70 year-old people, Hoff et al compared HTL in Swedish 70-year-olds over four decades and found substantial improvements over time [6]. Rosenhall, Möller & Hederstierna, however, referring to data from the same study in Gothenburg, stated that the hearing of 75-year olds had not changed over three decades [7].…”
Section: Introductionmentioning
confidence: 99%
“…When examining a new cohort of 70-year old participants in three previous cohorts, measured when at the same age, born in 1901-02, 1906-07 and 1922, both men and women in the new cohort showed improved hearing. The prevalence for women went from 37 % to 23 %, and for men from 53 % to 28 % (Hoff, Tengstrand, Sadeghi, Skoog, & Rosenhall, 2018). The decreased prevalence for men is probably because of a decrease in occupational noise exposure.…”
mentioning
confidence: 94%
“…Although rates of decline might not be that different, absolute differences seem to exist in Sweden, with 23 % of Swedish 70-year old women suffering from hearing loss while 28 % of men are affected (Hoff, Tengstrand, Sadeghi, Skoog, & Rosenhall, 2018). The impact of hearing loss on one's quality of life and ability to participate in society to a desired level might also affect men and women differently.…”
mentioning
confidence: 99%